Collateral vessel number, plaque burden, and functional decline in peripheral artery disease. (August 2014) - McDermott, Mary M; Carr, James; Liu, Kiang; Kramer, Christopher M; Yuan, Chun; Tian, Lu; Criqui, Michael H; Guralnik, Jack M; Ferrucci, Luigi; Zhao, Lihui; Xu, Dongxiang; Kibbe, Melina; et al.
Associations of collateral vessels and lower extremity plaque with functional decline are unknown. Among people with peripheral artery disease (PAD), we determined whether greater superficial femoral artery (SFA) plaque burden combined with fewer lower extremity collateral vessels was associated with faster functional decline, compared to less plaque and/or more numerous collateral vessels. A total of 226 participants with ankle–brachial index (ABI) <1.00 underwent magnetic resonance imaging of lower extremity collateral vessels and cross-sectional imaging of the proximal SFA. Participants were categorized as follows: Group 1 (best), maximum plaque area < median and collateral vessel number ≥6 (median); Group 2, maximum plaque area < median and collateral vessel number <6; Group 3, maximum plaque area > median and collateral vessel number ≥6; Group 4 (worst), maximum plaque area > median and collateral vessel number <6. Functional measures were performed at baseline and annually for 2 years. Analyses adjust for age, sex, race, comorbidities, and other confounders. Annual changes in usual-paced walking velocity were: Group 1, +0.01 m/s; Group 2, –0.02 m/s; Group 3, –0.01 m/s; Group 4, –0.05 m/s ( p -trend=0.008). Group 4 had greater decline than Group 1 ( p <0.001), Group 2 ( p =0.029), and Group 3 ( p =0.010). Similar trends were observed for fastest-paced 4-meter walking velocity ( p -trend=0.018). Results were not substantially changed when analyses were repeated with additional adjustment for ABI. However, there were no associations of SFA plaque burden and collateral vessel number with decline in 6-minute walk. In summary, a larger SFA plaque burden combined with fewer collateral vessels is associated with a faster decline in usual and fastest-paced walking velocity in PAD.